Study of voltage dips in distribution networks - Si, Wei (Nanyang Technological University, 2020)
The increasing technology in industry and commerce in modern society brings a big challenge to the power supply system. Some of the high-tech industry requires a higher power quality supply for their manufacturing works such as wafer, semiconductor and petrochemical industries. Among all the factors which affect the power quality, voltage dip is usually the biggest problem and commonly faced at the distribution and transmission networks. It might harm the end users’ equipment and cause the failure of production, resulting in the economic loss of the company. In this case, mitigation ways for voltage dips need to be sought to reduce the impact of voltage dips. By injecting a shunt current or series voltage is the usual way used to compensate the issues. In this study, voltage dips at bus bar will be simulated by using MATLAB and Simulink, and modeling of the different mitigation equipment will be done for STATCOM (static synchronous compensator), DVR (dynamic voltage restorer) and UPS (uninterruptable power supply). Different magnitudes and durations of voltage dips will be generated. The voltage waveform data will be collected to study the voltage restore times, and the voltage dip compensation performances and the total harmonic distortions (THD) will also be analyzed.